(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This scientific article delves into the intricate realms of information and information services, presenting a comprehensive analysis that spans philosophical, technological, and legal dimensions. The exploration unfolds the universal characteristics inherent in the cognitive process of forming scientific concepts, emphasizing the dynamic interplay between the exploration of properties-and-relations reality and the evolving needs associated with studying material systems. The term "information service" is scrutinized, revealing a lack of a universally accepted definition, prompting a nuanced understanding of the fundamental concept of "information." The multifaceted nature of information is elucidated through diverse perspectives, encompassing philosophical, technocratic, and pragmatic dimensions. Properties such as physical inalienability, replicability, and relevance are examined in the legal context, accentuating the economic value and legal significance of information. Despite the absence of a legislatively prescribed definition for "information service," scholars within civil law have engaged in defining the term, highlighting its diverse manifestations from basic provision to sophisticated processes. The article concludes by advocating for a unified terminology in consulting activities to mitigate ambiguities and enhance legal clarity.